Protocol for intelligent high-content screening of zebrafish embryos on a standard widefield screening microscope. (January 2017) - Peravali, Ravindra; Gehrig, Jochen; Giselbrecht, Stefan; Lütjohann, Dominic; Hadzhiev, Yavor; Müller, Ferenc; Liebel, Urban
Protocol Summary: Here we demonstrate a toolset for automated intelligent high-content screening of whole zebrafish embryos at cellular resolution on a standard wide-field screening microscope. Using custom-developed algorithms, predefined regions of interest, such as the brain, are automatically detected. The regions of interest are subsequently imaged automatically at high magnification, enabling rapid capture of cellular resolution data. standardized imaging of internal organs and cellular structures.